Estudo das contribuições do Pibid para a formação de professores de química no Brasil : análise de produções acadêmicas no período de 2010-2015 - Souza, Camila Carvalho de (2017)
This research, of documentary nature, addresses the contributions of the Institutional Program of Initiation Scholarship to Teaching - Pibid for the initial training of Teachers of Chemistry. In the form of a qualitative meta-analysis, 27 productions related to the impacts of Pibid were treated through Discursive Textual Analysis (ATD), between theses, dissertations, articles in periodicals and complete works in annals of events in the area of Chemistry Teaching, published in the period 2010-2015, encompassing the five regions of the national territory. The papers were previously selected according to their content, aiming to answer the research question of this investigation: What are the contributions of Pibid to the initial training of chemistry teachers in Brazil, present in academic productions in the period 2010-2015? The results obtained, by the analysis carried out, show actual contributions of the Pibid to initial teacher training in Chemistry, but also, they indicate impacts on the continuous training of supervisors and coordinators. Also, the contributions of the actions within the scope of the Pibid contemplated the Institutions of Higher Education through its courses of degree in Chemistry and the partner schools and their agents. It was possible to identify, also, situations problems to be overcome. Considering all these contributions, it was evident that the Pibid achieves the objectives set forth in the legal documents, and their actions are effective to improve: the initial teacher education in Chemistry; the curricular organization of Chemistry undergraduate courses; the teaching practices of supervising teachers; the teaching of Chemistry in partner public schools; the valuation of the teaching profession. The Pibid motivates graduates to follow the teaching career in Public Basic Education, overcoming the problems present in this profession. On the other hand, the Pibid, as a public policy, can not be seen as a solution to the complex problems of teacher training in the Brazilian educational context, because it does not meet all the subjects of this system.